Certi tesori esistono soltanto per chi batte per primo una strada nuova?: l’esperienza di novellini giovanni srl - Bonfanti, Angelo; Novellini, Valentina (Piccola Impresa / Small Business, 2011)
The case study proposes the history of Novellini Giovanni srl, food SME of the Italian East North, founded in 1978 by the homonym entrepreneur. The work shows that this enterprise has created a new category of product, a ready broth to use for the customers that desire to eat healthy and genuine, but don’t have time to devote to the kitchen stoves (Brodoè). Moreover, it examines the emergent threats and opportunity from the presence of multinationals (Gallina Blanca-Star Group), that they offer the same product (I Brodi). The analysis is conducted through a qualitative approach with an exploratory comparison of marketing and communication initiatives, adopted by the two enterprises to spread the value of the respective products on the market, allowing to delineate in strategic key the points of strength and the possible improvements of SME’s action